Theologica Paradoxa: Visdom og dårskab i Martin Luthers Heidelbergdisputation - Damgaard, Gustav (Dansk Teologisk Tidsskrift, 2024)
Abstract: This article discusses the role of experience in Martin Luther’s Heidelberg Disputation (1518). Drawing on the work of the post-hermeneutical theologian Günter Bader, the article develops Luther’s understanding of experience in a specific Hegelian sense. Hegel’s skeptical concept of experience allows for a dialectical understanding of the self-reversal of experience, which is summarized in the theological formula: “Erfahrung mit der Erfahrung”. This notion of experience is further contextualized through Luther’s theology of the cross. In conclusion the article discusses a possible speculative relation between language and experience in Luther’s theology.